EFISIENSI DAN EFEKTIFITAS PENGELOLAAN KEUANGAN DAERAH DI PROVINSI PAPUA : SUATU PENERAPAN DATA ENVELOPMENT ANALYSIS DI SEKTOR PENDIDIKAN - Yundy Hafizrianda (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2016)
In general, the purpose of this study was to assess the efficiency and effectiveness of Papua province public finance management in education sector. The specific purposes were: a) to describe and analyse the tendency in education sector budgeting as well as the outputs and outcomes of education development in Papua provincial government, regencies/municipality in Papua, and Papua as a whole; and b) to assess and analyse the efficiency of budget expenditures in education sector related to outputs and outcomes from the implementation of education development planning. The analysing tool used to assess efficiency and effectiveness of the regional finance was Data Envelopment Analysis (DEA). DEA is presented with correlation and determinant analysis. The study found that there was none from the 29 regencies/municipality in Papua that was identified to achieve efficiency in spending their expenditures simultaneously. Thus, none of these regencies and municipality was ideal, achieving synergy and integration in regional finance management in education sector. This revealed that the majority of regencies and municipality in Papua province encountered serious problems in managing their public finance particularly in education sector such as planning, budgeting, reporting, controlling, monitoring and evaluating. Another finding also showed that there was inadequate development in public expenditures management to achieve targeted outputs/outcomes such as increasing the ratio of numbers of teacher to students, level of graduates from national final examination, and numbers of school participants. However, there was a declining number of illiteracy and an increase of average length of study as well as number of full participation. Key words: Education sector expenditure, Efficiency, Effectiveness, Data Envelopment Analysis